Semantic support environment for research activity - Ismail, M.A.; Yaacob, M.; Kareem, S.A. (2008)
Scholarly activities are a collection of academic related activities such as research, teaching and consultation work which result in research outputs such as journals, theses and articles in proceedings. The output will then be disseminated to researchers all over the world by means of the WWW. The four pillars of this scholarship i.e. discovery, teaching, application, and integration of knowledge are supported by research activities which often start with the process of identifying key research questions. The ocean of information available on the internet could sometimes cause the scholars to be "lost in Cyber Ocean." Thus, this study aims at recognizing the key research questions and suggesting a support environment for scholarly activities for novice researchers. A structured interview was conducted among researchers to capture three pertinent aspects of research activities: becoming proficient in the new field of research, reviewing a research paper and identifying special research interests in specific research areas. The analysis of the interview shows pertinent questions that scholars make while carrying out their research. The feedback provides an overview of the range and altitude of support needed by scholars in seeking information especially in the electronic journal environment. Based on the result of the study, a proposal for system prototype and future work will be discussed. (Contains 2 figures and 5 tables.)